2024
DOI: 10.1097/tp.0000000000004881
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Kidney Transplantation Compared With Dialysis on Intima–media Thickness in Children—Results From the 4C-T Study

Carl Grabitz,
Rizky I. Sugianto,
Anke Doyon
et al.

Abstract: Background. Children requiring kidney replacement therapy experience high burden of cardiovascular (CV) disease leading to increased mortality. Intima–media thickness (IMT) indicating atherosclerosis is a validated surrogate marker for future CV events. Methods. We investigated the effect of different treatment modalities (dialysis, preemptive kidney transplantation (KTx), late KTx after dialysis) on IMT by multivariable linear mixed-effect modeling. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“… 29 Prospective studies in children have shown an improvement in BP and attenuated progression of cIMT with hemodiafiltration, 4 improved LV mass index 6-months after initiating hemodialysis, 30 and stable or even improving vascular measures with pre-emptive transplantation. 5 , 31 Despite antihypertensive medications, 60% of our cohort had uncontrolled hypertension. Further studies are required to explore the role of an earlier KRT start to limit preventable CV damage in cases where rigorous control of CV risk factors is not possible with medical management.…”
Section: Discussionmentioning
confidence: 94%
“… 29 Prospective studies in children have shown an improvement in BP and attenuated progression of cIMT with hemodiafiltration, 4 improved LV mass index 6-months after initiating hemodialysis, 30 and stable or even improving vascular measures with pre-emptive transplantation. 5 , 31 Despite antihypertensive medications, 60% of our cohort had uncontrolled hypertension. Further studies are required to explore the role of an earlier KRT start to limit preventable CV damage in cases where rigorous control of CV risk factors is not possible with medical management.…”
Section: Discussionmentioning
confidence: 94%